Human Capital Management: Paradigm Shift from Human Resource Management: Integrating HRM and KM Strategies for Effective Human Capital Management (Journal of Advances and Scholarly Researches in Allied Education, 2014)
The purpose of this paper is to contribute to theunderstanding of human capital management (HCM) and to make a case that it ismuch more than a new name for human resource management (HRM). The paperreviews the theoretical and empirical human capital (HC) literature, as well asthe literatures regarding strategic human resource management (SHRM), andknowledge management (KM) to develop a framework pertaining to the managementof HC.  The framework developed willassist researchers and practitioners in the identification and exploration ofvariables linked to the effective management of HC within organisations. It isconcluded that managers of organisations need to understand the complexity ofmanaging HC and must combine their HRM strategy with their KM strategy toleverage their human capital. By integrating several fields of the literaturethat relate to HC management, the paper suggests propositions that deservefuture research consideration.